Media Pembelajaran Mengenal Hewan Dalam Bahasa Inggris Berbasis Multimedia Interaktif - Ayuningtyas, Indri; Fadhilah, Muhammad Arief; Arifin, Rita Wahyuni (LPPM Universitas Islam 45 Bekasi, 2018)
Abstract The purpose of this instructional media design is to help teachers and students especially primary school children aged six and seven years in understanding the introduction of animal world in English. Animal introduction learning materials in English are used to be done without props, making it difficult for students to name the animals in English with good and correct spelling. Based on these problems then designed an interactive learning media as a companion of learning to be able to assist the process of acceptance of materials at school. Multimedia learning material development model used is Model Luther (Multimedia Development Life Cycle) is a model model developed through six stages are as follows: (1) concept, (2) design, (3) Material Collecting, (4) Assembly, (5) Testing, and (6) Distribution. But in this design is only new until the Assembly stage has not completed the stages of Testing and Distribution. Companion learning media is created using Adobe Photoshop, Adobe Illustrator and Adobe Flash CS 6. Keywords: Media Learning, Interactive Multimedia, Luther Model. Abstrak Tujuan dari perancangan media pembelajaran ini adalah membantu para guru dan murid khususnya anak sekolah dasar usia enam dan tujuh tahun dalam memahami pengenalan dunia satwa dalam bahasa inggris. Materi pembelajaran pengenalan hewan dalam bahasa inggris terbiasa dilakukan tanpa alat peraga sehingga menyulitkan bagi siswa dalam menyebutkan nama hewan dalam bahasa inggris dengan ejaan yang baik dan benar. Berdasarkan permasalahan diatas maka penulis mencoba membuatkan sebuah media pembelajaran interaktif dalam membantu proses pembelajaran pengenalan Hewan dalam bahasa Inggris. Model pengembangan materi pembelajaran multimedia yang digunakan adalah Model Luther (Multimedia Development Life Cycle) yaitu Model yang dikembangkan melalui enam tahap antara lain sebagai berikut: (1) concept, (2) design, (3) Material Collecting, (4) Assembly, (5) Testing, dan (6) Distribution. Namun dalam perancangan ini hanya baru sampai tahap Assembly dan belum menyelesaikan tahapan Testing dan Distribution. Media pembelajaran pendamping ini dibuat menggunakan Adobe Photoshop, Adobe Ilustrator dan Adobe Flash CS6 Kata kunci: Media Pembelajaran, Multimedia Interaktif, Model Luther